Pengaruh Kepemimpinan, Budaya Organisasi, dan Kesiapan Berubah terhadap Transformasi Digital di Industri Properti - Rinaldo, Rico; Arkeman, Yandra; Cahyadi, Eko Ruddy (Jurnal Manajemen dan Organisasi, 2025)
Digital transformation is inevitable for all global organizations as the technology grows rapidly. It has been significantly changing business landscape as well as business model. Digital transformation initiatives have been widely implemented by organizations in various global industries, however most of this efforts failed. Recent studies found that management is one of key factors attributed to the failure. This study aimed at analyzing the relationship between variables that influence digital transformation succes, in particularly in the property industry. It based on full range leadership model and supported by extension variables, such as organizational culture and readiness for change. 125 samples from mid managers of a property company were analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM). The result indicates that transformational leadership has a significant positive effect on digital transformation through organizational culture and readiness for change. This study suggests organization’s top management to encourage middle managers in implementing transformational leadership behaviors in order to achieve successful digital transformation.